Screen-Printed Electrodes on Tyvek Substrate as Low-Cost Device to Applications in Alzheimer's Disease Detection - Palley, Bianca Fortes; Artur, Julio Cesar; De Arruda, Milena Nakagawa; De Souza, Gustavo Freitas; Graves, David Alexandro; Bovolato, Ana Lívia De Carvalho [UNESP]; Deffune, Elenice [UNESP]; Schelp, Arthur Oscar [UNESP]; Gonçalves, Emerson Sarmento; De Moraes, Marli Leite (The Electrochemical Society, 2022)
Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized by impairment of cognitive functions and memory deterioration, which requires an early diagnosis for effective treatment. The use of immunosensors to detect Alzheimer s disease biomarkers stand out as a quick and cheap alternative for early detection of the disease. The development of Screen-Printed Electrodes (SPEs) meets a growing demand in the market for applications such as signal transducers in biosensor devices. In this work was development a method for fabrication of low cost SPE for application in the detection of Alzheimer s disease through autoantibodies. It was produced microelectrodes on polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF) and high-density polyethylene (HDPE) manufactured by DuPont Tyvek®substrates. SPEs produced on Tyvek®substrates have shown promising results for low-cost, disposable and flexible sensors. The carbon paste showed excellent adhesion to Tyvek®substrate and the electrodes produced showed an electrochemical performance comparable to commercial electrodes, besides reproducible. The detection results showed that it is possible to detect anti-Aβ40 autoantibodies in real samples of serum and cerebrospinal fluid using the electrode modified with two bilayers of (PEI/(DDPG + Aβ40)) since the capacitance increased more in positive sample with the presence of autoantibody than in negative samples.